2021
DOI: 10.1111/dth.15016
|View full text |Cite
|
Sign up to set email alerts
|

Topicalbeta‐blockersin dermatologic therapy

Abstract: An increasing use of beta-blockers in dermatology has been described over the last 10 years, despite the fact that their use in diseases other than infantile hemangiomas is off-label. This review discusses the emerging role of topical beta-blockers in the treatment of infantile hemangioma, but also pyogenic granuloma, Kaposi sarcoma, wounds and nail paronychia. Data in literature demonstrate that topical beta-blockers are a safe and valid therapeutic option in numerous cutaneous diseases. Side effects are main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…They can postpone or obviate surgical treatment, especially in children, for whom they are the first-line treatment, also, in large lesions by reducing its size. The only limitation of beta-blockers here is their inability to perform histological examinations [ 48 ]. Although the adverse effects and systemic absorption appeared to be negligible in all included studies, further research is needed to identify the maximal dosage and duration.…”
Section: Discussionmentioning
confidence: 99%
“…They can postpone or obviate surgical treatment, especially in children, for whom they are the first-line treatment, also, in large lesions by reducing its size. The only limitation of beta-blockers here is their inability to perform histological examinations [ 48 ]. Although the adverse effects and systemic absorption appeared to be negligible in all included studies, further research is needed to identify the maximal dosage and duration.…”
Section: Discussionmentioning
confidence: 99%
“…22 Owning to growing evidences and clinical experiences, increasing topical beta-blocker use in dermatologic disease is described in recent decade including hemangioma, Kaposi sarcoma, wound healing, paronychia and pseudopyogenic granuloma. 23 Olamiju et al demonstrated a case series with 10 EGFR-TKI-related paronychia patients who were treated with topical timolol 0.5% twice daily under occlusion. Nine patients needed adjunct dermatologic therapy including topical antibiotic, steroid or even silver nitrate cauterization.…”
Section: Discussionmentioning
confidence: 99%
“…Eczema, ulcers, skin rashes, desquamation, and erythema are frequent adverse effects of topical timolol (Filoni et al, 2021). A large recent study in over 700 superficial IHs reported that 3.9% of patients treated with oral propranolol (2 mg/kg/day) presented systemic adverse events (AEs) while topical timolol treatment (0.5% hydrogel, three times daily) did not cause AEs (Wu et al, 2018).…”
Section: Adverse Eventsmentioning
confidence: 99%